The Comparison of Alexithymia and Emotions Control among Substance Abusers and Healthy People - M.J Bagyan Kouleh Marz; M Narimani; S Soltani; A.R. Mehrabi (Drug Control Headquarters, Research and Education Office, 2014)
Objective: The purpose of the present study was to compare Alexithymia and emotional control among substance abusers and healthy people. Method: The research design was causal-comparative research design which is categorized as descriptive research method. The population included of all people who were referred to addiction treatment centers in Noor-Abad city (Delfan). The participants of the study comprised of 50 addicts under treatment and 50 healthy participants who were matched based on age, education level, social-economical status, and number of children selected by available sampling method. The alexithymia (TAS-20) and emotions control scales administered among both groups. Results: The results showed that there is a significant difference between addicts and non-addicts groups in terms of alexithymia and emotional control. In addition, difficulty in identifying of feelings, depression, anxiety and anger were the most important predictors of addiction severity. Conclusion: These results show that any difficulty in expressing emotions and disability in controlling of negative emotions (anger, depression, and anxiety) are risk factors for substance abuse.